Factors associated with the worsening of COVID-19 symptoms among cohorts in community- or home-isolation care in southern Thailand - Sila, Thanit; Suriyaamorn, Wisanuwee; Toh, Chanavee; Rajborirug, Songyos; Surasombatpattana, Smonrapat; Thongsuksai, Paramee; Kongkamol, Chanon; Chusri, Sarunyou; Sornsenee, Phoomjai; Wuthisuthimethawee, Prasit; Chaowanawong, Raya; Sangkhathat, Surasak; et al. (Frontiers in Public Health, 2024)
Although factors such as the presence of underlying diseases have been evaluated to assess coronavirus disease (COVID-19) severity, factors such as vaccinations and treatments also need to be considered. This study aimed to investigate the factors associated with the time-to-referral due to worsening symptoms in 8,638 patients with laboratory-confirmed COVID-19 quarantined in home or community isolation. Age ≥60 years, neurologic disorders, cardiovascular disease, and human immunodeficiency virus infection as significant risk factors for severe COVID-19 referral. Full-or booster-dose vaccinated patients had a lower risk of experiencing severe symptoms than unvaccinated patients. Moreover, those receiving the combination vaccine during the Omicron-dominant period had a substantially lower time-to-referral than those unvaccinated during the Delta-dominant period. Furthermore, those vaccinated between 1-6 months prior to infection had a substantially lower risk of time-to-referral than that of the reference group. The time-to-referral of individuals vaccinated <1 month or >6 months prior to infection was similar to that of the unvaccinated group. These findings emphasize the importance of vaccination efficacy and early intervention in high-risk patients with COVID-19, to reduce symptom severity. This study provides important insights to guide future epidemic management strategies and optimize patient care during infectious disease outbreaks.